Sex differences in athletic performance: Perspectives on transgender athletes - Nokoff, N. J.; Senefeld, J.; Krausz, C.; Hunter, S.; Joyner, M. (Exercise and Sport Sciences Reviews, 2023)
Sex hormone concentrations, particularly testosterone, are primary determinants of sex-based differences in athletic and sports performance, and this relationship may inform fair competition and participation for athletes. This article describes the sex-based dichotomy in testosterone and the implications for sex-based differences in individual sports performance, including factors that relate to athletic performance for transgender individuals, and areas of future investigation.